The Upsurge of Impact Factors in Pediatric Journals Post COVID-19 Outbreak: A Cross-Sectional Study - Mondal, Pritish; Mazur, Lauren; Su, Lilly; Gope, Suparna; Dell, Esther (Frontiers in Research Metrics and Analytics, 2022)
Background: Impact factor (IF) is a quantitative tool designed to evaluate scientific journals’ excellence. There is an unprecedented upsurge in biomedical journals' IF in 2020, perhaps contributed by the increased number of publications since the COVID-19 outbreak. We conducted a cross-sectional study (2018-20) to analyze recent trends in standard bibliometrics (IF, Eigenfactor, SNIP) of pediatric journals. We also estimated reference and publication counts of biomedical journals since publication volume determines the number of citations offered and IF. Methods: Various bibliometrics of pediatric journals and reference/publication volumes of biomedical journals were compared between 2020 vs. 2019 and 2019 vs. 2018. We also compared open access (OA) and subscription journals' trends. Finally, IF changes in the journals of a different specialty, pulmonology, were estimated. Results: The study included 164 pediatric and 4918 biomedical journals (OA=1473, subscription=3445). Pediatric journals' IFs had increased significantly in 2020 (median (IQR)= 2.35(1.34)) vs. 2019 (1.82(1.22)) (Wilcoxon: p-value<0.001). IFs were unchanged between 2018 and 2019. Eigenfactor remained stable between 2018-2020, while SNIP was increased progressively. Reference/publication volumes of biomedical journals escalated between 2018-2020, and OA journals experienced faster growth than subscription journals. IFs of pulmonary journals also increased considerably in 2020 vs. 2019. Conclusions: We report an upsurge in pediatric journals’ IF, perhaps contributed by a sudden increase in publication numbers in 2020. Therefore, considering this limitation, IF should be cautiously used as the benchmark of excellence. Unlike IF, Eigenfactor remained stable between 2018-2020. Similar changes in IF were also observed among the journals of another specialty, pulmonology.